SDSS-IV MaNGA: global stellar population and gradients for about 2000 early-type and spiral galaxies on the mass–size plane. Issue 2 (9th February 2018) - Li, Hongyu; Mao, Shude; Cappellari, Michele; Ge, Junqiang; Long, R J; Li, Ran; Mo, H J; Li, Cheng; Zheng, Zheng; Bundy, Kevin; Thomas, Daniel; Brownstein, Joel R; et al.
Abstract: We perform full spectrum fitting stellar population analysis and Jeans Anisotropic modelling of the stellar kinematics for about 2000 early-type galaxies (ETGs) and spiral galaxies from the MaNGA DR14 sample. Galaxies with different morphologies are found to be located on a remarkably tight mass plane which is close to the prediction of the virial theorem, extending previous results for ETGs. By examining an inclined projection ('the mass–size' plane), we find that spiral and early-type galaxies occupy different regions on the plane, and their stellar population properties (i.e. age, metallicity, and stellar mass-to-light ratio) vary systematically along roughly the direction of velocity dispersion, which is a proxy for the bulge fraction. Galaxies with higher velocity dispersions have typically older ages, larger stellar mass-to-light ratios and are more metal rich, which indicates that galaxies increase their bulge fractions as their stellar populations age and become enriched chemically. The age and stellar mass-to-light ratio gradients for low-mass galaxies in our sample tend to be positive (centre < outer), while the gradients for most massive galaxies are negative. The metallicity gradients show a clear peak around velocity dispersion log10 σe ≈ 2.0, which corresponds to the critical mass ∼3 × 10 10 M⊙ of the break in the mass–size relation. Spiral galaxies with large mass and size have the steepest gradients, while the most massive ETGs, especially above the critical mass M crit ≳ 2 × 10 11 M⊙, where slow rotator ETGs start dominating, have much flatter gradients. This may be due to differences in their evolution histories, e.g. mergers.